PENGEMBANGAN VIDEO PEMBELAJARAN SISTEM PENGAPIAN SEPEDA MOTOR FI UNTUK SISWA DI SMK - Haris Handoko; Nurcholish Arifin Handoyono; Samsul Hadi (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2026)
The limited availability of instructional media can affect students’ understanding of the material, particularly in practical learning such as the motorcycle fuel injection (FI) ignition system. This study aims to develop and assess the feasibility of an instructional video on the FI ignition system for Grade XI students of the Motorcycle Engineering and Business (TBSM) program at SMK Muhammadiyah 1 Bambanglipuro. The research employed the Research and Development (R&D) approach using the 4D model, which includes the stages of Define, Design, Develop, and Disseminate. The research subjects consisted of material and media experts from the Vocational and Technical Education Department, Universitas Sarjanawiyata Tamansiswa (UST), as validators, and 32 students as media users. Data were collected using validation questionnaires and analyzed quantitatively to determine the media’s feasibility. The validation results showed that the instructional video received scores of 84% from material experts, 85% from media experts, and 89% from students, all of which fall into the “highly feasible” category. Based on these findings, the developed instructional video is proven to be effective and feasible as a supporting medium to enhance students’ conceptual and practical understanding of the FI ignition system in vocational schools.